Design and development of wearable fluidic antenna with AMC - Muhammad Nazrin Ramli author (School of Computer and Communication Engineering, 2018)
The main objectives of the study are as follows: to develop a wearable fluidic antenna operating in the Wireless Local Area Network (WLAN) and Industrial, Scientific and Medical (ISM) 2.45 GHz and 5.8 GHz bands using liquid metal and flexible polymer-based substrate for improved water resistance and wetness; to develop a wearable fluidic antenna with AMC with SAR of less than 2 W/kg, based on European regulatory requirements; to fabricate and evaluate the wearable fluidic antenna in terms of performance in free space and on body.